A systematic survey of Internet of Things frameworks for smart city applications. (August 2022) - Peralta Abadía, José Joaquín; Walther, Christian; Osman, Ammar; Smarsly, Kay
Highlights: Sustainable IoT technologies have only been reported in few IoT frameworks Less than half of the IoT frameworks target interoperability and scalability Security has been addressed by means of authentication but encryption is lacking Sustainability should be a main focus in IoT frameworks for smart city applications A novel five-layered IoT framework concept for smart city applications is proposed Abstract: Recent developments in smart sensing technologies have fostered the wide-spread utilization of smart city applications, which rely on Internet of Things (IoT) frameworks to work efficiently. The terms "smart city" and "IoT framework", however, have been given several definitions, without consensus. Consequently, definitions of the terms "smart city" and "IoT framework" need to be condensed, consolidating concepts and guidelines of smart cities and IoT frameworks, as will be shown in this study. In addition, a systematic survey of IoT frameworks for smart city applications is presented, summarizing and comparing the technologies and architectures of IoT frameworks for smart city applications. As a result of this study, trends in IoT frameworks for smart city applications and a definition of the term "smart city" are provided. Materializing the findings achieved in this study, an abstract IoT framework concept for smart city applications is proposed. It is expected that the definition of the term "smart city" may be used as a basis for a generally accepted formal definition and that the proposed IoT framework concept may provide a strong foundation for successful IoT framework implementations in the context of smart city applications.